Seasonal Variation of Water Quality at Sungai Chanteq and Sungai Dendong - Saiful Iskandar, Khalit; Azman, Azid; Fathurrahman, Lananan; Noor Afiza, Badaluddin (2018)
Water is important for all living things as water is one of the components build up in plant, animal and human. Rivers are an important source for domestic, industrial as well as agriculture sector. The aim of this study to assess the physicochemical and biological parameter from two rivers located at Pasir akar and Tembila. Water Quality Index (WQI) related to the quality status of the water. Two sampling stations in different rivers were sampled from December 2017 until March 2018. Eight water quality parameters were analyzed based on in-situ and ex-situ analysis at two different time. This experiment conducted according to HACH and American Public Health Association (APHA) methods. Based on the Malaysia WQI, the shows the classification water quality value for Sungai Dendong and Sungai Chanteq are 71.56 (class III) and 89.99 (class II), respectively. Based on the water class and guideline treatment of Malaysia, class II for water quality need conventional requirement to treat the water, while class III need extensive treatment to serve in the agricultural sector surround the area.